Learning, Teaching, and Researching in Shadow Education in Hong Kong: An Autobiographical Narrative Inquiry. (March 2019) - Yung, Kevin Wai-Ho
Purpose: This article aims to illustrate from the author's insider perspective the lived experiences of engaging in private tutoring in Hong Kong as a tutee, a tutor, and a researcher and draw implications on several issues arising from the prevalence of shadow education. Design/Approach/Methods: This article adopted an autobiographical narrative approach. Data were collected through the author's memoir of events, stimulated by the tutorial materials he used when he was a tutee and a tutor, his own video-recorded lessons of tutoring, and reflective journals from his research projects. Findings: Various issues are discussed based on the narrative of the author playing different roles in the tutoring industry, including (1) the positive and negative washback on mainstream education, (2) the lack of strict regulation of the quality of tutors and advertisements, and (3) how shadow education may exacerbate education inequality and how some tutorial companies and nonprofit organizations are addressing the issue. Originality/Value: This article, to the best of the author's knowledge, is the only one that discusses the issues of shadow education from an author's own personal experiences as a tutee, a tutor, and a researcher. It illustrates how practices and policies of the private tutoring industry are evolving in Hong Kong from an insider perspective.